THE DEVELOPMENT OF HEALTH LITERACY FOR RISK COMMUNICATION OF CORONAVIRUS DISEASE 2019 AMONG VILLAGE HEALTH - Riyaboot , Nattakan; Khotaphan , Phlaophilas (Primary Health Care Journal (Northeastern Edition), 2022)
The research aimed to the development of health literacy for risk communication of coronavirus disease 2019 among village health volunteers in Mueang Nong Khai district, Nong Khai province. The study was divided into 3 phases, i.e., Phase 1: Studying the situation and health literacy for risk communication of coronavirus disease 2019 among village health volunteers; Phase 2: Creation and development of the health literacy promotion program for risk communication of coronavirus disease 2019 among village health volunteers; and Phase 3: Trial of the health literacy promotion program for risk communication of coronavirus disease 2019 among 35 village health volunteers. The research implementation took 8 weeks. The statistics data analysis were frequency, percentage, mean, standard deviation, and Paired samples t-test. The results showed that: The results showed that: Phase 1: The overall health literacy for risk communication of coronavirus disease 2019 was high (82.74). Phase 2: Creation and development of the health literacy promotion program for risk communication of coronavirus disease 2019 included the learning management plan of 6 activities, i.e., 1) mind map of data survey in communities, 2) reading comprehension of the worksheet and infographics, 3) scenario-based learning management, 4) practice of data comparison and reliability test, 5) learning the pattern of the self-management practice for disease control project, and 6) creating awareness of data verification before use or forwarding and, Phase 3: The results of the trial of the health literacy promotion program for risk communication of coronavirus disease 2019 among village health volunteers revealed that health literacy and readiness of village health volunteers toward coronavirus disease 2019 surveillance and prevention during the post-trial was significantly higher than the pre-trial with statistically significant (P-value < .05).